Global warming and allergy - Kahramanoğlu, Fatih; Kahramanoğlu, Pakize İrem (Scientific Reports in Medicine, 2026)
Climate change, triggered by anthropogenic carbon dioxide emissions, may lead to increased morbidity and mortality in allergic diseases due to factors such as elevated and novel pollen production, storms, high temperatures, migration with exposure to air pollution, increased humidity, indoor mold and fungal proliferation, ozone elevation, biodiversity loss, and alterations in the microbiota. Strategies should be developed to reduce greenhouse gases and chemical and biological air pollutants, to inform the public accurately, and to implement preventive and therapeutic measures during high-allergen seasons.